Reflections about school dropout in Finland and Puerto Rico - Viana, Nancy; Rullán, Agustín (Education Policy Analysis Archives, 2010)
This work presents reflections about some key factors that help to understand the reasons why in Finland school dropouts are practically nonexistent, while in Puerto Rico they are a significant problem. Several reasons that explain this situation were found. Finland has good student support services, teachers have more academic freedom, social inequalities exist in a smaller scale, schooling including university, and health services are free, and teacher training is more rigorous. Based on the findings of this study, we developed a model to understand school dropout as a complex social system. To develop this model we used a causal diagram, a tool from the theory of dynamic systems.